2012
DOI: 10.1080/17405629.2012.673266
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of personality and identity in adolescence

Abstract: Portions of this chapter will be published as: Klimstra, T. A., Hale, W. W., Raaijmakers, Q. A. W., Branje, S. J. T., & Meeus, W. H. J. (in press). Personality assessment and maturation. In R. J. R. Levesque (Ed.), Encyclopedia of adolescence. Heidelberg, Germany: SpringerVerlag. General Introduction 12 Chapter 1. General introductionWhen persons describe themselves, they are typically referring to certain characteristics, such as "outgoing", "nervous", "messy", "friendly" and "creative". Exactly these kinds o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 222 publications
(685 reference statements)
0
9
0
1
Order By: Relevance
“…The conscientiousness component of personality traits, addressed in this study, includes features such as hard-working, task-based behavior, motivation, caution, determination, and self-discipline. Individuals with high conscientiousness are punctual, orderly, patient, purposeful, and planned (Klimstra, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The conscientiousness component of personality traits, addressed in this study, includes features such as hard-working, task-based behavior, motivation, caution, determination, and self-discipline. Individuals with high conscientiousness are punctual, orderly, patient, purposeful, and planned (Klimstra, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…But the Big-Five Personality Theory, which suggests personality traits can be assessed under the five-factor, has begun to come to the fore (1,2). Many researchers (3)(4)(5)(6)(7)(8) agree about focus of personality can be grouped under five dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…Openness to experience which another of the five factors includes traits such as creativity, curiosity, and openness to new ideas. People high in openness to experience are imaginative and sensitive (1,2,(8)(9)(10). Studies (1,(11)(12)(13) examined relations between depression, anxiety, aggression, loneliness, and self-esteem indicated that five personality factors negatively related to psychological problems, and positively related to psychological variables.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Lilgendahl's (this volume) chapter takes on a perennial question: what is the relation between identity and personality? There have been numerous empirical studies over the years examining the relations between identity status classifications and personality traits (e.g., extraversion, openness; see Klimstra, 2012). These studies, however, have not led to a very sophisticated understanding of the similarities and differences between these two constructs.…”
Section: Discussionmentioning
confidence: 99%